2002
DOI: 10.1037/0735-7044.116.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral differences among 129 substrains: Implications for knockout and transgenic mice.

Abstract: Most knockout (KO) mice are produced with embryonic stem cells derived from a 129 strain. Because most KO strains are backcrossed to B6 yet retain a portion of their genome from 129, especially around the ablated target locus, phenotypes previously attributed to the ablated locus may be due to passenger 129 genes. Thus, the authors decided to test several 129 substrains for their behavioral characteristics. Seven 129 substrains were put through a battery of tasks to determine their behavioral profiles. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
97
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 36 publications
17
97
3
1
Order By: Relevance
“…However, Cook et al (2002) found that contextual and cued fear conditioning were normal in 129P1/ReJ mice compared with C57BL/6J mice. Thus, it is unlikely that the genetic contribution of 129P1/ReJ to the 9XCA/Wah strain is the sole cause of altered hippocampal synaptic transmission and impaired memory extinction.…”
Section: Discussionmentioning
confidence: 97%
“…However, Cook et al (2002) found that contextual and cued fear conditioning were normal in 129P1/ReJ mice compared with C57BL/6J mice. Thus, it is unlikely that the genetic contribution of 129P1/ReJ to the 9XCA/Wah strain is the sole cause of altered hippocampal synaptic transmission and impaired memory extinction.…”
Section: Discussionmentioning
confidence: 97%
“…Symptomatic YAC128 mice also showed deficits in open-field habituation, a simple test of learning and memory (Gerlai et al, 1996;Bolivar et al, 2000;Cook et al, 2002). At 8 months of age, YAC128 mice were hypoactive compared with WT mice.…”
Section: Cognitive Deficits In Symptomatic Yac128 Micementioning
confidence: 99%
“…This is an element of context that only a handful of laboratories have used (Cook et al 2002;Wrenn et al 2002;Balogh and Wehner 2003;Bothe et al 2004;Gould et al 2004), and we believe it reduced effects unrelated to tone-shock associations by making the contexts more distinguishable. Although the visual (checkered vs. solid colored walls) and tactile elements (smooth vs. grid floor; square vs. octagon shape) yielded discriminable contexts in the Initial Protocol, as reflected in the different levels of freezing to the two contexts in the initial study, the addition of odor to one of the two contexts during the Final Protocol provided a distinguishing element in a sensory modality that is highly salient to mice (Doty 1986;Beauchamp and Yamazaki 2003;Breer 2003).…”
Section: Modification Of Experimental Parameters Reduced Nonassociatimentioning
confidence: 99%